2012
DOI: 10.5194/nhess-12-631-2012
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of skewness and kurtosis of weakly nonlinear unidirectional waves over a sloping bottom

Abstract: Abstract.We consider the effect of slowly varying depth on the values of skewness and kurtosis of weakly nonlinear irregular waves propagating from deeper to shallower water. It is known that the equilibrium value of kurtosis decreases with decreasing depth for waves propagating on constant depth. Waves propagating over a sloping bottom must continually adjust toward a new equilibrium state. We demonstrate that weakly nonlinear waves may need a considerable horizontal propagation distance in order to adjust to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 33 publications
8
49
0
Order By: Relevance
“…In some situations a significant increase in the rogue wave occurrence was observed indeed, though in other cases no significant changes were found. Zeng and Trulsen (2012) considered a "deeper" regime (kh > 1.2) of wave evolution compared to numerical simulations by Sergeeva et al (2011) (kh < 0.4) and exposed the reduced kurtosis and skewness for the shallower region of transformation. Laboratory experiments of Trulsen et al (2012) embrace the "transitional" zone when the waves travel from an intermediate depth to the shallow water with kh down to 0.54.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some situations a significant increase in the rogue wave occurrence was observed indeed, though in other cases no significant changes were found. Zeng and Trulsen (2012) considered a "deeper" regime (kh > 1.2) of wave evolution compared to numerical simulations by Sergeeva et al (2011) (kh < 0.4) and exposed the reduced kurtosis and skewness for the shallower region of transformation. Laboratory experiments of Trulsen et al (2012) embrace the "transitional" zone when the waves travel from an intermediate depth to the shallow water with kh down to 0.54.…”
Section: Discussionmentioning
confidence: 99%
“…A suitable model is the nonlinear Schrödinger equation (NLS) for the case of wave evolution in space over uneven depth. The impact of bathymetry is taken into account through depth-dependent coefficients and a shoaling term (Djordjevic and Redekopp, 1978;Zeng and Trulsen, 2012): …”
Section: Simulation Of Weakly Nonlinear Waves Over Variable Bottommentioning
confidence: 99%
See 1 more Smart Citation
“…Although the characteristics of freak wave occurrence and its prediction in deep water regions become getting clear, there are a few studies about the characteristics of freak wave propagating from deep to shallow water regions (e.g. Janssen and Onorato, 2007;Zeng and Trulsen, 2012;Trulsen et al, 2012). The most of previous studies assumed a flat bottom and quasi stationary conditions for given water depth.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that the reason of rogue wave occurrence is because of the interaction of quasisoliton coherent structures. Meanwhile, Zeng & Trulsen 59 developed a NLSE for uneven bottom to simulate random waves propagating over 143L0 for 159 T0, and indicated that a change of water depth can provoke a spatially non-uniform distribution of kurtosis on the lee side of the slope. More recently, Sergeeva,et al 60 simulated random waves in coastal regions on a scale of 20~40 L0 for up to 80 T0 based on a variable CNLSE, and found that rogue waves are likely to occur at deeper locations.…”
Section: Introductionmentioning
confidence: 99%